Investigation of the Gap Between Patients' Perceptions and Expectations of Hospital Service Quality - Haniyeh Nazem; Hadi Raeis Abdollahi; Abasat Mirzaei (Iran University of Medical Sciences, 2020)
Background: Health care services are costly and complex and provide facilities that significantly affect the economy and quality of life of individuals. In this study, we determined the gap between patients' expectations and perceptions of hospital service quality to provide reference data for creating strategies to improve health care quality. Methods: In this descriptive cross-sectional study, five private hospitals in Tehran were selected. Using a simple random sampling method, 110 patients were recruited and voluntarily responded to the standard service quality (SERVQUAL) model questionnaire. Data were analyzed by the K-S test, t-test, and paired t-test using SPSS V. 23. Results: The results showed that among the quality of health care components, the highest mean was related to the responsiveness (M=3.89) and the least was related to the tangible dimension (M=3.11). The lowest average quality gap (perceived service and expected service) was seen in the responsiveness dimension (2.96 and 3.28) and followed by reliability (2.66 and 3.90), tangible (2.53 and 3.91), empathy (1.36, 3.19), and assurance dimensions (2.39 and 4.75). Conclusion: The findings revealed a significant difference between the patients' perceived and expected services, which indicates that the quality of services as perceived by patients was lower than their expectations. According to the findings, the assurance dimension had the greatest gap. To reduce or eliminate the existing gap, it is suggested that hospitals consider strategic and operational planning to improve hospitalization experience‏, quality of medical services, and hospital resources.